A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.